Numerical and Experimental Investigation of a Vortex Head for Back-Pressure Suppression in Petroleum Pumping Systems - Samuel Oliver Effiom; Maria Kaka Etete Enoh; Godwin Effiong Willie; Precious-Chibuzo Effiom (Scientific Journal of Engineering Research, 2026)
Back-pressure accumulation and transient pressure surges remain critical operational challenges in petroleum pumping systems, particularly during high-rate product transfer into storage tanks. Conventional mitigation strategies such as pressure relief valves, surge vessels, and bypass lines are largely reactive, energy-intensive, and maintenance-dependent. Despite advances in computational fluid dynamics (CFD), limited research has addressed passive inlet-based hydrodynamic conditioning for petroleum storage tanks with full-scale industrial validation. This study presents a combined numerical and experimental investigation of a passive vortex head (VH) designed to suppress back pressure through vortex-induced flow redistribution at the tank inlet. Three-dimensional CFD simulations were performed using ANSYS Fluent with the realizable k–ε turbulence model to analyze pressure distribution, velocity fields, turbulence characteristics, and vortex formation. Controlled experimental validation was conducted using a prototype system under normalized inlet pressure conditions (0.07 bar) in an industrial petroleum storage facility. The results demonstrate that the vortex head induces a stable swirling flow that promotes gradual momentum dissipation and reduces localized pressure buildup near full capacity. Compared with a conventional straight inlet configuration, the vortex head reduced peak back pressure by approximately 20–30%, while decreasing total tank filling time by about 15% under identical flow conditions. CFD predictions agreed with experimental measurements within ±5%. The findings establish passive vortex-based inlet conditioning as a practical, energy-efficient strategy for preventive back-pressure suppression in petroleum storage infrastructure.